Instructional Feedback Analysis of an Online Virtual Language Learning Platform Through EZ-Arabic among Malaysian Teachers of Primary Schools - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal (Excellence in Research for Australia (ERA)- ERA Journal ID- 200679, 2019)
The use of online educational courseware serves as an important teaching and learning aid among digital generation. It is increasingly becoming the focus of researchers in designing and developing new and up-to-date educational aids that cater to the learning needs of 21st century learners as well as keeping in-line with the transformation of latest technologies. This paper aims to analyze instructional feedback of an online virtual language learning platform through EZ-Arabic among Malaysian teachers of primary schools. It is a virtual Arabic virtual learning platform which is specifically designed for primary school?s learners in Malaysia. The respondents were purposively selected from 118 primary school teachers by using an adapted survey related to this study via an online virtual learning platform from 11 Jun until 22 October 2016. This interactive Arabic virtual learning tool prototype enables teachers and students access to additional Arabic language learning aids that complement traditional learning methods. It facilitates Arabic learning enhancement through a compendium and a variety of open-sources of learning tools such as e-book of Arabic text books, educational games, audio-video learning aids, online translator, online chat-box for discussion, link of Arabic keyboard for typing purpose, and links of various websites in learning Arabic for children. General findings indicate that teachers show a very good preference of using virtual language learning platform in teaching Arabic by using computer programmes with mixed competency levels and usages of ICT skills. Moreover, the respondents show promising expectation in using mobile learning. The implication of this study is to help educational stakeholders to better understand issues related to teaching and learning implementation of e-learning in their institutions.